Optimization Of Composite Hinges For Aircraft Spoiler Using Finite Element Method - Razali, Amirul Herman (2019)
Current hinge brackets for A320 aircraft are made from metallic materials. The change of material from metallic to composite can reduce the structure weight. The classical method of analysis such as hand calculation and actual testing are not recommended for the new composite hinge design because it leads to high production and testing cost, as well as longer time consumption. This thesis is concerned with the method of modelling and analysing composite hinge bracket for A320 Spoiler using finite element method. The reverse engineering method through MSC PATRAN software is used to benchmark the actual loadings, constraints and allowable stress for the new hinge. Then, the method of optimization using Hypermesh software is used to avoid trial and error method, which requires a lot of efforts and more time. Next, a prototype of composite hinge is developed to validate the weight of the panel. The comparison of results between the old and the new design is done which records a reduction of 32% of the weight. This result proves that the simulation method proposed in this research is indeed feasible to be used for preliminary design stage for the hinge bracket of A320 Spoiler